The Impact of Customer Testimonials and Brand Trust in Women's Hijab Repurchase Intention in Cirebon - Umiyaroh; Oktavani, Icha Dinda Lestari; Fatimah, Siska Ernawati; Maulany, Soesanty (School of Business, IPB University (SB-IPB), 2025)
Background: The hijab industry in Indonesia is rapidly growing, leading to intense online and offline competition between brands.Purpose: This study measures Repurchase Intention based on customer testimonials and brand trust in hijab products marketed through TikTok Shop, Shopee, Lazada, Bukalapak, and other marketplaces.Design/methodology/approach: This study used a quantitative method with data from 400 female hijab users aged 15–24 years in Cirebon. Owing to its strength in complex model analysis, SEM-PLS was applied to analyze the effect of customer testimonials and brand trust on repurchase intention.Findings/Results: This study indicates that customer testimonials and brand trust positively influence repurchase intention for hijab products in Cirebon. The impact of customer testimonials on repurchase intention had a coefficient of 0.400, whereas brand trust demonstrated a more substantial influence with a coefficient of 0.417. The findings suggest that brand trust has a more significant impact on encouraging repurchase behaviour than customer testimonials. These results underscore the importance of building strong brand trust through consistent product quality, excellent customer service, and positive brand reputation. For hijab business owners, effective marketing strategies should generate positive customer testimonials and ensure that the customer experience aligns with the brand’s promises. By consistently delivering quality and maintaining reliable service, businesses can foster consumer trust, enhance customer loyalty, and sustain repurchase intentions over the long term.Conclusion: These two independent variables simultaneously drive Repurchase Intention for hijab products. Brand Trust had a more substantial influence on the intention to repurchase the hijab.Originality/value (State of the art): Consumers trust brands for various reasons, including good product or service quality and brand reputation. Brand trust is a crucial factor in long-term relationships with customers. Keywords: customer testimonials, brand trust, repurchase intention, marketplace, hijab